MicroRNA-29b/c-3p Indicate Advanced Liver Fibrosis/Cirrhosis in Univentricular Heart Patients With and Without Fontan Palliation - Abu-Halima, Masood; Meese, Eckart; Saleh, Mohamad Ali; Keller, Andreas; Abdul-Khaliq, Hashim; Raedle-Hurst, Tanja (Frontiers in Cardiovascular Medicine, 2021)
Abstract Aim: The present study aims to identify those microRNAs (miRNAs) in patients with univentricular heart (UVH) disease with and without Fontan palliation that may be associated with advanced liver fibrosis/cirrhosis. Materials and Methods: SurePrint™ 8×60K Human v21 miRNA arrays were used to determine the miRNA abundance profiles in the blood of 48 UVH patients with and without Fontan palliation and 32 matched healthy controls. The abundance levels of selected miRNAs have been validated by quantitative reverse transcription-polymerase chain reaction (RT-qPCR). Results: According to microarray analysis, 50 miRNAs were found to be significantly abundant in UVH patients of which miR-29b-3p and miR-29c-3p were significantly related to the model of end-stage liver disease (MELD)-Albumin and albumin-bilirubin (ALBI) score representing advanced liver fibrosis/cirrhosis. Relative expression levels of both miRNAs were significantly higher in patients with a higher collapsibility index representing venous hepatic congestion, a higher MELD-Albumin or ALBI score and incomplete or no Fontan palliation. In the logistic regression analysis, a MELD-Albumin score ≥ 11 or ALBI score > −2.6 were best predicted by total bilirubin (OR 6.630, P=0.016), albumin (OR 0.424, P=0.026) and miR-29c-3p (OR 33.060, P=0.047). After adjustment to the status of Fontan palliation, however, no statistical significance of these parameters was found thus underlining the importance of palliation status on progression of liver fibrosis/ cirrhosis in UVH patients. Conclusions: In UVH patients with and without Fontan palliation, miR-29b-3p and miR-29c-3p seem to be markers of advanced liver fibrosis/cirrhosis and thus may be used in the risk assessment of these patients.